Quality of life in natural and built environment an introductory analysis - Mohit, Mohammad Abdul (Elsevier, 2013)
Quality of life (QOL) is a multifaceted concept used by a variety of disciplines and at different spatial levels. The theoretical aspect of QOL relates to happiness, life satisfaction and needs satisfaction approaches. It is a complex construct, and its measurement is multidimensional. QOL researchers use either objective or subjective measurement or a combination of the two, through modeling exercises. It is also an expanding area of research. Many disciplines have embedded QOL within their researches. Nevertheless, in Built Environment, such as Architecture, Landscape Architecture, Quantity Surveying, Applied Art, QOL-related researches are few. Therefore, it is recommended that QOL research should be embedded in these branches of the Built Environment.